Assessment of genotoxicity of aflatoxin M1 and B1 contaminated milks after in vitro human digestion - Ladeira, Carina (2016)
Introduction - Milk is considered a complete food from the nutritional point of view. Milk can be exposed to various types of contamination, such as mycotoxins. These metabolites are naturally occurring toxic compounds produced by fungi. Several studies on milk samples have reported the presence of aflatoxin B1 (AFB1) and M1 (AFM1), due to the high incidence in samples intended for human consumption, carcinogenicity proven AFB1 and resistance of the contaminants to the process of digestion, making those available for intestinal absorption. Considering these aspects, the objective of this study was to evaluate the genotoxicity of milk samples contaminated by AFB1 and AFM1 before and after the action of lactic acid bacteria using Caco-2 intestinal human cells.